Socialization of Eradication of Hijaiyah Illiteracy and Guidance of Gersik Village, Jagoi Babang District - Buyung Buyung; Mariyam Mariyam; Dina Anika Marhayani; Evinna Cinda Hendriyana; Eka Murdani (STKIP Singkawang, 2019)
The level of education of the people is still low and the number of illiterates and Arabic letters for the Muslim community is still high. There are still many people in Gresik Village in Jagoi Babang District who cannot read Hijaiyah letters. Conditions that occur in a society consisting of age -up and children. In order to eradicate the illiteracy of the Hijaiyah letters , various methods are carried out so that it is easy and can be learned or understood by every Muslim who has not been able to read the Holy Qur'an,. Effort undertaken to face these challenges include the illiteracy eradication program for people who already have a low level of formal education. Therefore, one of the initial steps done is to implement a program of socialization eradication Arabic letters on the community, especially the W arga Coarse sand . Activity is more effectively facilitate Villagers Coarse sand in order to foster interest for who can not read the letters hijaiyah mempelaj ari how to read the Quran. The objectives of the PKM-M program include eradicating Arabic illiteracy, increasing insight andknowledge, increase the ability and awareness of self potential in the community of Gresik Village and provide motivation for Hijaiyah letters. The implementation of community service includes several methods, namely lectures, questions and answers, practice and evaluation. with the socialization of a good impact on the understanding of the letter hijaiyah and foster interest in reading al-Quran with easier-aided guidance . the conclusion of the activity had a good impact on the understanding of hijaiyah letters from the people of Gresik Village. With the community service activities of STKIP Singkawang, the people of Gersik Village felt helped.